MEMBANGUN KESADARAN MASYARAKAT HIDUP SEHAT SERTA LINGKUNGAN BERSIH MELALUI KKM DI DESA JAGAMUKTI KECAMATAN SURADE KABUPATEN SUKABUMI 2024 - wianto, Asep; Purwanti Basuki (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2025)
Student Work Lecture (KKM) is a form of community service carried out by students in implementing the Tri Dharma of Higher Education, which of course is carried out in every final program of learning on campus, with the aim or hope that students will be more mature with their scientific discipline when they are directly involved in the midst of society which in reality that national and state life is very complex and dynamic, then students must be able to overcome and provide a positive impact in other words they must become agents of change in the future. The Health Sector in a clean environment is a special concern for the author because healthy living and a clean environment are the basis for humans wherever they are to be able to do or do activities with a feeling of comfort, safety, and health, the Health factor is the key to human survival, whether we realize it or not, we all expect a healthy life and a clean environment, then other life needs will be met properly. There are several factors that cause low public awareness and motivation to protect the environment from various environmental problems, especially waste generated from various community activities, including: a, Lack of public awareness to protect the environment, b, lack of waste disposal sites, c. lack of socialization about clean living, d. Life behavior that blames each other. There is not a single human being on this earth who expects to be sick and suffer so that it can have a big impact or impact on life or living, from various problems that arise due to unhealthy lifestyles and are influenced by a dirty environment, and as if not responsible for themselves, thus the author concentrates on the problem of a healthy environment, by motivating the Jagamukti village community, especially the Jagamukti hamlet, Jagamukti Village, Surade District, to maintain and preserve a clean environment, in order to achieve a good level of public health.